OC-SLAM: Steadily Tracking and Mapping in Dynamic Environments - Wu, Zhenyu; Deng, Xiangyu; Li, Shengming; Li, Yingshun (Frontiers in Energy Research, 2021)
Visual SLAM is mainly used in real-time localization and mapping tasks of robots in various complex environments, while traditional monocular vision algorithms are struggling to cope with weak texture and dynamic scenes. To solve these problems, this work presents an object detection and clustering assisted SLAM algorithm (OC-SLAM), which adopts the YOLO-Fastest object detection algorithm to add semantic information to the image and conducts geometrical constraint on the dynamic keypoints in the prediction box to optimize the camera pose. It also uses RGB-D camera to perform dense point cloud reconstruction with the dynamic objects rejected, and facilitate European clustering of dense point clouds to jointly eliminate dynamic features combining with object detection algorithm. Experiments in the TUM dataset indicate that OC-SLAM enhances the localization accuracy of the SLAM system in the dynamic environments compared with ORB-SLAM2 and it has shown impressive performance in the localizition and can build a more precise dense point cloud map in dynamic scenes.